Nepal’s Role in Strengthening SAARC - Bhattarai, Kamal Dev (Journal of Foreign Affairs, 2021)
This study seeks to examine the overall efforts undertaken by Nepal to activate the South Asian Association for Regional Cooperation (SAARC), particularly after the indefinite postponement of its 19th Summit that was scheduled to take place in Islamabad, Pakistan, on November 9-10, 2016. As a strong proponent of regionalism and regional cooperation, Nepal’s position has always been making the regional body vibrant and result-oriented; and Nepal has been relentlessly working for the same since its very inception. Much has been written about SAARC and Nepal, still very little literature is available that sincerely digs out the concrete efforts made by Nepal to strengthen the SAARC process. Therefore, this study tries to fulfill this gap. Additionally, this aims to make policy prescriptions for the revival and strengthening of SAARC. The study consists of both primary and secondary data collected from books, seminar papers, policy briefs and newspapers. It applies both qualitative and quantitative approaches while analysing Nepal’s efforts in strengthening the SAARC process.